Problems of Improving the Organizational and Economic Mechanism of Management of Food Industry Enterprises - Boyquzieva Gulsanam Adxamovna (Periodica Journal, 2022)
The article presents the results of research on the study of the specific characteristics of agricultural production in modern conditions, the determination of factors for increasing the efficiency of business activity in the agro-industrial complex, the justification of the need to increase the efficiency of production, and the application of a problem-oriented approach to the management of business structures. The article examines the specific characteristics of agriculture, without taking into account the necessary efficiency of business structures operating in it. Solving the problems of the modern development of agricultural production, and increasing the competitiveness of local enterprises in connection with membership in the World Trade Organization (WTO) is closely related to the identification of such characteristics and the establishment of their influence (encouragement or limitation). is based on dependence. the final results of the activities of economic entities in the agro-industrial complex.
Keywords: security; management mechanism; production